Gini Who? The Relationship between Inequality Perceptions and Life Satisfaction - Daniele Marchesi; Milena Nikolova; Viola Angelini (Institute of Labor Economics (IZA), 2024)
Research on the consequences of income inequality on subjective well-being has yielded mixed results, including a lack of a statistically significant correlation. We propose that this inconsistency may arise from the failure to differentiate between perceived and actual income inequality. Perceptions of inequality matter because individuals often do not know the actual level of inequality in their country. Leveraging data from the 2016 Life in Transition Survey, which includes unique information on individuals' inequality perceptions, we find a positive association between these perceptions and life satisfaction across 33 countries. Individuals who believe that inequality has increased in the previous 4 years are on average 8% less satisfied with their life (on a 1-5 scale) compared to respondents who perceive no increase in inequality. The magnitude of the estimate is sizeable, being twice as large as the influence of unemployment. Taking actual inequality levels and changes into account does not alter the conclusions, suggesting that inequality perception matters for life satisfaction above and beyond actual inequality. Our findings survive a battery of robustness checks, including an instrumental variables approach and addressing common method variance bias. We also find that mobility expectations and fairness perceptions cushion but do not fully offset the negative association between perceived inequality increases and life satisfaction. Our findings imply that understanding the role of inequality perceptions can be key to improving social cohesion and individual and societal well-being.
Keywords: D63; E31; I31; 330; inequality; perceptions; life satisfaction; subjective well-being